(untitled) (Proceedings of the Society of Antiquaries of Scotland, 1852)
Mr. W.H. Scott communicated Mr. Henry Laing’s account of an unpublished seal and counter-seal of Kilwinning Abbey. Based on its lettering style, Gothic, Laing surmises that the seal is early 14th century, whereas the counter-seal appears to be of lower standard of craftsmanship and thus, according to Laing of a later date. Scott and Laing disagree on the conclusions that can be reached on the basis of this evidence, Laing thinking the original counter-seal had been lost and hastily replaced, Scott that it was a deliberate change.